Perancangan Game Story “Inner Threads” Sebagai Media Edukasi Kesehatan Mental Pada Generasi Muda Di Indonesia - Laila; Ahmad Khoirul Anwar; Yudi Wibowo (JURNAL KEMADHA, 2026)
ABSTRACTMental health is a crucial aspect of individual well-being, yet it is a pressing concernamong Indonesia's younger generation. Data from the 2022 I-NAMHS shows that34.9% of adolescents experience mental health issues, with 5.5% diagnosed with amental disorder. Studies also indicate that cases of mental disorders, particularlyanxiety and depression, peak in early adulthood (21-23 years). However, it is still only2.6% of adolescents who access services. Globally, the WHO identifies adolescents asbeing at high risk for mental disorders, with depression being the leading cause ofdisability and suicide the leading cause of death among those aged 15-29. In responseto this gap, this project developed "Inner Threads," an interactive visual novel game asa medium for mental health education. The game targets late adolescents and youngadults in Indonesia, highlighting issues of emotional management and burnout, as wellas the importance of professional support. This approach aligns with Generation Z'spreference for digital technology and gaming. This is supported by an interest survey,which showed 84.7% of respondents were interested. The development of "InnerThreads" used the Multimedia Development Life Cycle (MDLC) method. The finalresults showed that this game was effective in conveying an educational message andincreasing user awareness, empathy, and understanding of mental health issues. Thiseffectiveness was demonstrated by playtest results with respondents aged 18-24, wherethe majority felt a substantial emotional impact, found the story relevant, andappreciated the visuals and music that supported the immersive experience. This gamesuccessfully triggered self-reflection, fostered awareness of the importance of supportfrom those around them, and even motivated them to seek professional support.Keywords: Mental Health, Adolescents, Early Adults, Educational Games, VisualNovels, Inner Threads, Indonesia.